Autonomy-Supportive Teaching in the Large Ensemble: Positive Outcomes for Student Motivation and Teacher Satisfaction. (June 2022) - Butler, Timothy
Autonomy-supportive teaching, self-determination theory, and self-regulated learning can be effective methods for increasing student motivation in a range of classroom settings. However, music educators struggle to apply principles of student autonomy in ensemble rehearsals. Using intent-based leadership as a practical model for guiding students toward self-directed habits, I describe one approach to shape self-sufficient student musicians in the ensemble setting. By creatively harnessing students' capacity for independent learning, their musical skills and motivation for music learning can improve dramatically.